Quantization-based event-triggered control for synchronization of 2-D discrete-time switched master-slave systems in Roesser model - Zhou, Zhimin; Shi, Lei; Liu, Wenbo; Luo, Xilong; Mo, Shiqi; Mou, Jiayin (Nonlinear Analysis: Modelling and Control, 2026)
This paper investigates synchronization control for 2-D discrete-time switched master-slave systems modeled by the Roesser framework, which is classic for spatiotemporal dynamics in 2-D systems. A novel quantization-based event-triggered control strategy is proposed to handle complexities from switching dynamics, discrete-time features, and spatial coupling, while considering limited communication resources. By designing a mode-dependent event-triggered strategy and constructing mode-dependent Lyapunov functions for horizontal and vertical dynamics, new sufficient conditions are derived to ensure global exponential synchronization (GES) of the system. The approach relaxes strict stability requirements for individual modes, allowing global stability even with unstable modes. Additionally, the integration of quantization techniques and event-triggered mechanisms significantly reduces data transmission, thereby optimizing network bandwidth usage. Numerical simulations verify the method’s effectiveness.
Keywords: 2-D switched systems; event-triggered control; quantization; synchronization; stability